Peran Akuntansi dalam Pengambilan Keputusan Bisnis di Era Digital - Annisa Fitriah Mudassir (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This paper discusses in depth the role of accounting in business decision-making in the digital era, as well as the challenges and opportunities faced by the accounting profession in the context of rapid and complex technological developments. In the modern business world, accounting information plays a crucial role, not only as a financial reporting tool but also as a foundation for strategic analysis that can influence the direction and policies of an organization. The issues raised pertain to the importance of timely and accurate accounting information in supporting managerial decision-making, as well as how this information can be used to enhance the performance and competitiveness of companies. The main objective of this research is to explore how digitalization and technological innovations, such as artificial intelligence (AI), big data analytics, and cloud-based information systems, affect accounting practices and their impact on business decision-making. This research also aims to identify the challenges arising from technological changes, including data security issues, the necessary technological skills, and regulatory changes that accountants must face. The methodology employed in this research is a normative approach with descriptive analysis, which includes literature studies and analysis of various relevant secondary data sources. Additionally, this research presents several case studies to demonstrate the application of theory in real practice and its impact on decision-making. The findings indicate that although digitalization brings many benefits in terms of efficiency and accuracy, there are serious challenges to be faced, such as the increased risk of data breaches and the need for higher technological skills among accounting professionals. The conclusion drawn from this research is that to optimally leverage the potential of accounting in supporting business decision-making, companies must invest in training and skill development for their accountants. Furthermore, the importance of implementing sustainable accounting practices is increasingly gaining attention, especially in the context of social and environmental responsibility. Thus, accounting not only functions as a supporting tool but also as a strategic element that adds value to companies in facing the complexities and uncertainties of the future.